Association of Entrepreneurship Ecosystem with Economic Growth in Selected Countries: An Empirical Exploration - Singh, Ajay K; Ashraf, Shah Nawaz (Journal of Entrepreneurship, Business and Economics, 2020)
This study was created the entrepreneurship ecosystem index (EEI) as an effective tool for measurement of entrepreneurship ecosystem for 34 selected economies during 2000-2017. It was considered EEI as an integrated index of 12 different indicators (i.e. financing for entrepreneurs, governmental support and policies, taxes and bureaucracy, governmental programs, basic school entrepreneurial education and training, post school entrepreneurial education and training, R&D transfer, commercial and professional infrastructure, internal market dynamics, internal market openness, physical and services infrastructure, and cultural and social norms) of entrepreneurship activities. Composite Z-score technique was used to create EEI for undertaken economies. Thereupon, it assesses the association of estimated EEI with socio-economic, science & technology (S&T) and IPRs related factors using correlation coefficient techniques. Estimated values of EEI show that India has 8th position in entrepreneurship ecosystem among the 34 economies. Also, there was found a high diversity in entrepreneurship ecosystem in efficiency, factor and innovation driven economies due to variation in 12 indicators of entrepreneurship ecosystem and socio-economic activities. Accordingly, it investigates the causal relationship between EEI and per capita GDP using linear, non-linear and log-linear regression models at country-wise panel data. Empirical results imply that per capita GDP is significantly associated with entrepreneurship ecosystem, socio-economic, S&T and IPRs related indicators. Entrepreneurship ecosystem have a causal relationship with per capita GDP. Entrepreneurship ecosystem is significantly associated with socio-economic development and S&T and IPRs related indicators. It brings several practical policy proposals to create effective entrepreneurship ecosystem, and to sustain economic and social development in India. Research paper Keywords: Entrepreneurship ecosystem; Science & Technology, Intellectual property rights; Per capita GDP; Economic development; India; Developed and developing economies Reference to this paper should be made as follows: Singh, A. K., & Ashraf, S. N. (2020). Association of Entrepreneurship Ecosystem with Economic Growth in Selected Countries: An Empirical Exploration, Journal of Entrepreneurship, Business and Economics , 8 (2), 36–92.